One-dish wonders : 150 fresh takes on the classic casserole - Bonvissuto, Danny S. (Oxmoor House, 2015)
"The casserole is never going out of style. These one pan dishes have remained perennial favorites for their convenience, comfort, and the simple fact that sometimes you can just stash one in your freezer for when you just can't figure out what to make for dinner some night or when company unexpectedly shows up! Now, the editors of Southern Living have put together this must-have casserole cookbook featuring recipes that use fresh, whole ingredients, and interesting flavors, while still building on the ease and versatility that has made the dish so popular for years."--provided by publisher.